The romantic comedy and its film location: do perceptions differ? - Quintal, Vanessa; Roff, Elizabeth (Detay Anatolia Akademik Yayincilik Danismanlik Org. Turz. Ltd, 2012)
This paper examines how viewers of a romantic comedy set in New York differ in their perception and intention to visit New York. The sample comprised 230 film viewers at an Australian cinema. Male viewers perceived significantly higher performance/ financial, social and physical risk when travelling to New York. This may be because male viewers who had visited New York previously, did so less recently and spent less time there than female viewers. Examining how a film impacts on perceptions about a place is relevant to the film and tourism industries. First, it can help film makers and destination managers in delivering consistent messages about a film and its location. Second, it provides researchers with a theoretical basis for future empirical studies.